Dinosaur teeth from the Lower Cretaceous Jiufotang Formation of western Liaoning, China - Yin, Ya-Lei; Li, Yang; Hu, Jin; Zhang, Hong-Gang (PeerJ, 2025)
Here, two dinosaur teeth are discovered from the Lower Cretaceous Jiufotang Formation in Longcheng, Chaoyang, western Liaoning, China. This discovery marks a new fossil site for the Jehol Biota, characterized by three-dimensionally preserved fossils. Based on comprehensive morphological comparisons, the teeth can be assigned to Theropoda and early-diverging Titanosauriformes. The theropod tooth, with a preserved length of 47.8 mm, represents a distinct taxon separate from Sinotyrannus, which is the only known large theropod dinosaur from the Jiufotang Formation. The titanosauriform tooth represents the youngest sauropod record within the Jehol Biota. These findings contribute to an increased dinosaur diversity within the Jiufotang Formation from ten taxa to 12.
Keywords: Titanosauriform; Theropod; Tooth; Jehol Biota; Western Liaoning